TAMI-48. THE KETOGENIC DIET IS INEFFECTIVE IN PRECLINICAL MODELS OF IDH1 WILD-TYPE AND IDH1 MUTANT GLIOMA. (12th November 2021) - Javier, Rodrigo; Horbinski, Craig
Abstract: Despite decades of intensive research, infiltrative gliomas are still usually lethal and challenging to treat. A subset of gliomas contains mutations in isocitrate dehydrogenase 1 (IDH1 mut ), which disrupts cellular biochemistry; such gliomas are generally less aggressive than their IDH1 wild-type (IDH1 wt ) counterparts. Some preclinical studies have suggested that a ketogenic diet (KD), characterized by low-carbohydrate and high-fat content, may be beneficial against a variety of cancers, including gliomas. However, not all studies have shown promising results, and to date, no study has addressed the sensitivity of glioma cells to KD in the specific context of the endogenous IDH1 mut metabolic landscape. The aim of the current study was to compare the effects of KD in preclinical models to IDH1 wt versus IDH1 mut gliomas. In vitro treatment of patient-derived IDH1 wt and IDH1 mut glioma cells with the ketone body β-hydroxybutyrate showed no significant effect on cell proliferation in a low glucose culture environment. Likewise, the in vivo flank growth rates of these patient-derived IDH1 wt and IDH1 mut glioma xenografts showed no significant difference when mice were fed KD versus regular diet (GBM12 p=0.98, GBM164 p=0.4, GBM196 p=0.11). Finally, KD had no effect on the survival of mice engrafted with isogenic Sleeping-Beauty transposase-engineered IDH1 wt (median control survival 22 days versus treatment 23 days, p=0.23) or IDH1 mut glioma cells (median control survival 26.5 days versus treatment 26 days, p=0.81). These data suggest that IDH1 mut gliomas are not more responsive than IDH1 wt gliomas to KD, and that clinical trials further exploring KD in this subset of glioma patients are probably not warranted.